1999
DOI: 10.1016/s0005-2736(99)00014-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interactions of the synthetic N-terminal peptide of HIV-1 gp41 and its structural analogs

Abstract: Structural and functional studies assessed the membrane actions of the N terminus of HIV-1 glycoprotein 41000 (gp41). Earlier site-directed mutagenesis has shown that key amino acid changes in this gp41 domain inhibit viral infection and syncytia formation. Here, a synthetic peptide corresponding to the N terminus of gp41 (FP; 23 residues, 519-541), and also FP analogs (FP520V/E with Val-->Glu at residue 520; FP527L/R with Leu-->Arg at 527; FP529F/Y with Phe-->Tyr at 529; and FPCLP1 with FP truncated at 525) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 74 publications
7
83
1
Order By: Relevance
“…These studies not only confirm the predicted high affinity of MTRs for the membrane interface, but also support their role as promoters of lipid bilayer destabilization [12,13,34,[36][37][38]. In principle MTR-s might promote fusion by reducing the formation energies of the lipidic intermediates of fusion, and/or by accelerating the opening of fusion pores [39][40][41].…”
Section: Introduction: Membrane-transferring Regions Within the Glsupporting
confidence: 67%
“…These studies not only confirm the predicted high affinity of MTRs for the membrane interface, but also support their role as promoters of lipid bilayer destabilization [12,13,34,[36][37][38]. In principle MTR-s might promote fusion by reducing the formation energies of the lipidic intermediates of fusion, and/or by accelerating the opening of fusion pores [39][40][41].…”
Section: Introduction: Membrane-transferring Regions Within the Glsupporting
confidence: 67%
“…These studies have shown that the FP aggregates in solution, 23,[27][28][29][30] and readily binds to and inserts into membranes, 23,27,[29][30][31][32][33][34] aggregating therein. 23,30,[33][34][35] Additionally, the FP induces aggregation, 23,31,36,37 and destabilization, 23,[27][28][29][30][31][34][35][36][37][38][39][40][41][42] of membrane vesicles; functions that allude to a direct role during viral fusion. Structural characterization of the discrete FP has revealed seemingly paradoxical data; a-helix or b-structure.…”
Section: Introductionmentioning
confidence: 99%
“…Structural characterization of the discrete FP has revealed seemingly paradoxical data; a-helix or b-structure. 27,[29][30][31][32][33][34][35][37][38][39][41][42][43][44][45] This apparent dichotomy may be explained by structural plasticity inherent in the FP based on its primary sequence, which is highly enriched in Gly and Ala (Figure 2). During the fusion event, both structures may be relevant and serve specific Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these soluble ectodomain structures, the protein is trimeric, and its three N-termini (corresponding to about residue 30 in the whole envelope protein) are in close proximity at the end of an in-register helical coiled-coil. These structures end several residues C-terminal of the fusion peptide, and it has therefore been hypothesized that during viral/target cell fusion, at least three fusion peptides insert into the target cell membrane with their C-termini in close proximity.A variety of experimental methods have shown that both the HIV-1 and influenza fusion peptides can assume helical or nonhelical structures in their membrane-associated forms (6,9,10,14,15,17,18,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) 1,phosphatidylethanolamine; N-Rh-PE, N-(lissamine rhodamine B sulfonyl)phosphatidylethanolamine; PDB, Protein Data Bank; PI, phosphatidylinositol; POPC, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine; POPE, 1-palmitoyl-2-oleoyl-snglycero-3-phosphoethanolamine; POPS, 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-L-serine; rf, radio frequency; RET, resonance energy transfer; REDOR, rotational-echo double resonance; RFDR, radio frequencydriven dipolar recoupling; SEDRA, simple excitation for the dephasing of rotational-echo amplitudes; SIMPSON, simulation program for solidstate NMR spectroscopy; TFA, trifluoroacetic acid; TPPM, two pulse phase modulation; 1D, one dimensional; 2D, two dimensional. …”
mentioning
confidence: 99%